Policy And Practice For Global Tourism (Madrid, Spain : World Tourism Organization, 2022)
Policy and Practice for Global Tourism is a guide to the major themes in world tourism today. Through 11 chapters, it presents an overview of topics ranging from sustainable tourism to social networks or emerging markets to creating a successful destination brand. Examples of UNWTO’s work in key areas are highlighted throughout the publication, and these are complimented by case studies and opinions from business leaders, destinations management organizations, academics and NGOs. Policy and Practice for Global Tourism is aimed at decision makers working in the public and private sectors alike, as well as those who are simply interested in learning more about this fast-moving and dynamic sector of the global economy.